The Gen Z's Participation in Cooperatives: Do Interest and Experience Matter? - Lelo Sintani; Noorjaya Nahan; Aston Pakpahan (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Research on Generation Z and their contributions to economic activities is always intriguing to discuss, particularly efforts that can be undertaken to enhance their participation in economic growth. This study explores the roles of interest and experience as cooperative members within schools on the participation of Generation Z as cooperative members in Palangka Raya, Indonesia. Engaging 150 high school students, this research adopts a quantitative survey design to gather data concerning the interest, experience, and participation of Generation Z. The analysis results indicate that the interest and experience of Generation Z as cooperative members in schools significantly positively influence their participation at the community level. High interest fosters internal motivation, while positive experiences cultivate deep emotional and cognitive bonds with the cooperative. The combination of both yields a stronger positive impact. These findings offer insights for the development of cooperative programs in schools and regional government strategies to motivate Generation Z to actively engage in cooperative activities.